PENGARUH PESAN IKLAN SLO DENGAN SIKAP KHALAYAK TERHADAP KEINGINAN MEMBUAT SLO - Windhi Tia Saputra; Witanti Prihatiningsih (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
This research discusses about the public service announcements message from the Ministry of Energy and Mineral Resources (ESDM). Subject of this research is Sertifikat Laik Operasi (SLO) advertisement. The purpose of this study was to determine the effect of SLO advertising messages exposure with public attitudes towards the desire to apply SLO. This study uses a quantitative method with linear regression analysis. The population in this study were active students of FISIP UPN